Understanding the structure-band gap relationship in SrZrS3 at elevated temperatures: a detailed NPT MD study. Issue 33 (8th August 2022) - Jaykhedkar, Namrata; Bystrický, Roman; Sýkora, Milan; Bučko, Tomáš
Abstract : Thermal effects on the structure and electronic band gap of the needle-like and distorted perovskite phases of SrZrS3 were investigated over the temperature range 300–1200 K by means of ML-accelerated ab initio molecular dynamics in an NPT ensemble. Abstract : Thermal effects on the structure, bulk modulus ( B 0 ), and electronic band gap ( E g ) of the needle-like (NL) (NH4 CdCl3 structure type) and distorted perovskite (DP) (GdFeO3 structure type) phases of SrZrS3 were investigated over the temperature range 300–1200 K by means of ab initio molecular dynamics in an NPT ensemble, accelerated by adaptive machine learning. An anisotropic thermal expansion of a distinctly different quality was observed for the two phases. While all lattice vectors of the NL phase expand monotonously with T, the thermal behavior of the DP phase is more complex, with two vectors (b and c ) monotonously expanding and one (a ) contracting after an initial expansion. We show that the thermally-induced structural changes in the DP phase are a consequence of proximity of the cubic phase (C), into which it transforms quasi-continuously upon heating. A linear decrease of B 0 with T (from 45.9 GPa to 33.6 GPa for NL and from 66.8 GPa to 48.5 GPa for DP) is predicted. Since the temperature dependent E g values are determined as the NPT ensemble averages, both the lattice expansion and the electron–phonon coupling effects are naturally taken into account in our simulations. We found that the E g for NL is nearly constant, while that for DP decreases by as much as ∼0.5 eV within the studied temperature range. The latter is shown to be almost exclusively due to a very large atomic displacement contribution resulting from the proximity of the parent C phase, with the E g ∼ 0.8 eV lower than that of the DP phase.